Smart City Evolution: Integrating Technology and Governance for Sustainability in Benguerir - Chaouki CHOURAIK (Journal of Information Sciences)
This review paper investigates the progression of smart cities, emphasizing the amalgamation of technology, governance, and sustainable development. It delves into the historical roots of smart cities, the pivotal role of Information and Communication Technologies (ICTs), and the significance of robust governance frameworks in urban planning. The case study of Benguerir, a Moroccan smart city, exemplifies successful initiatives while also addressing challenges such as rapid urbanization and technological advancement. The review underscores the necessity for comprehensive strategies that incorporate environmental, social, and economic sustainability principles. Future research and practice implications include innovative financing models and enhanced stakeholder collaboration. Recommendations for policymakers, urban planners, and other stakeholders highlight the importance of prioritizing sustainability, inclusive decision-making, and investment in resilient infrastructure. By adopting these principles, cities can progress towards a more prosperous, equitable, and sustainable future.